Contrast enhancement of magnetic resonance imaging (MRI) of polymer gel dosimeter by adding Platinum nano- particles - Deyhimihaghighi, N.; Mohd Noor, Noramaliza; Soltani, Nader; Jorfi, Rahele; Haghiri, Maryam Erfani; Adenan, Mohd Zulfadli; Saion, Elias; Khandaker, Mayeen Uddin (Institute of Physics Publishing, 2014)
In this research different concentrations of Platinum nanoparticles (Pt-NPs) embedded in PAGAT polymer gel and irradiated with Cobalt -60 (60Co). The OD of samples indicate significant dose enhancement caused by Pt-NPs. Different concentrations of Pt-NPs were investigated: 0.5×10−2,1×10−2 2×10−2 and 3×10−2 mg/l and these were presented the enhancement in OD by the factor of 11.56, 27.10, 15.84 and 10.07 respectively. As the mean energy of 60Co is 1.25 MeV and atomic number (Z) of Pt is 78, the predominant effect will be Compton effect and Photoelectric cannot occurred. This work studied the feasibility of using PAGAT polymer gel combined with Pt-NPs as a suitable tool to perform dosimetric investigation of nanoparticles application in radiotherapy as dosimeter and dose enhancer.